THE EFFECTIVENESS OF LOWER POLE LIGATION IN TONSILLECTOMY - Muhammad Saleem; Khizar Saleem; Danish Hassnain; Baber Raﬁque; Nisar Akbar Khan (Journal of University Medical & Dental College, 2019)
OBJECTIVE: Hemorrhage following tonsillectomy has always been a serious problem. Recently several techniques, devices and materials have been developed to reduce the intra-operative and post-operative blood loss but still no optimal methods have emerged. In this study we assessed the eﬀectiveness of lower pole ligation in tonsillectomy ensuring the hemostasis and preventing the post-operative hemorrhage in early and late stages.MATERIALS AND METHODS: This was a hospital based retrospective study performed in the department of ENT, Aziz Fatima Hospital (Medical College) and Faisal Hospital Faisalabad from May 2014 to June 2017. During this period 310 patients underwent tonsillectomy using COLD DISSECTION TECHNIQUE. Inferior pole was ligated by Negus artery forceps as close to its junction with the lingual tonsils ensuring no tissue remnants are left and knot applied by Negus ligature carrier with Black Silk #1. Bipolar diathermy was used for tonsillar bed hemostasis. Follow-up was continued for the next 4 weeks.RESULTS: Out of 310 patients undergoing the procedure only 2 presented with reactionary hemorrhage. One of them presented after 3 hours and the cause of bleeding was appreciated as slipping of the knot from the lower pole which was shifted to OT and ligated again using the Silk # 1. Second patient presented after 2 hours with mild reactionary hemorrhage and the site was not from the lower pole, but diﬀuse oozing from the tonsillar bed which was conservatively dealt by cold sponging and ice cold gargles. Out of 310 only 1 patient presented after 3 weeks with secondary hemorrhage which was treated by broad spectrum antibiotics.CONCLUSION: The use of lower pole ligation in tonsillectomy aﬀords eﬃcient and practical hemostasis. The procedure is inexpensive and requires no special and reﬁned equipment. The anterior and posterior tonsillar pillars remained intact thus the functional anatomy was preserved.